Empowering Inclusive and Sustainable Educational Transformation Through Learning Communities and School Supervision - Suyanto, Suyanto; Fakhruddin, Fakhruddin; Khafid, Muhammad (Universitas Negeri Semarang, 2025)
This paper explores how integrated roles of school supervision, educational facilitation, and learning community evaluation can significantly contribute to realizing inclusive and equitable quality education for all. Grounded in the Indonesian context of the Driving Schools Program and the emergence of grassroots learning communities. The study aims to analyze the impacts of systemic support provided by school supervisors and facilitators in transforming school culture and pedagogy. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation from several public and private junior secondary schools. The findings highlight the importance of collaborative supervision, reflective learning cycles, and evidence-based mentoring in enhancing teacher professionalism and student-centered practices. The study underscores the pivotal role of learning communities as dynamic ecosystems to sustain educational change and promote equity. This paper contributes to the discourse on education for all by offering practical insights on how leadership moderation, contextualized facilitation, and community-based monitoring can advance inclusive education systems.